La voirie médiévale du site de la Citadelle (Amiens) : étude archéologique et historique (xiie-xvie siècle) - Mathieu Béghin; Francesca Rapone (Bulletin du Centre d’Études Médiévales d’Auxerre, 2016)
In France and abroad, medieval road networks have rarely been studied and the few existing studies rather deal with economics, public health, or legislative framework than technical aspects. An extra muros road network has recently been discovered during the excavations on the Citadelle site in Amiens. The technical and material characteristics of the discovered roads and their developments are studied from and archeological and historical approach. Written sources and findings allow to describe and explain the changes and improvements of the road network between the XIIth and XVIth centuries, that urban development, topography and building of the gate fortifications have made necessary.